SYNCHRONIZATION OF CARBOHYDRATE AND PROTEIN SUPPLY IN THE SUGARCANE BAGASSE BASED RATION ON IN SITU NUTRIENT DEGRADABILITY - Sani, F. F.; Nuswantara, L. K.; Pangestu, E.; Wahyono, F.; Achmadi, J. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
Two adult male sheeps fitted with rumen cannula were used in two experiments to study the effects of synchronization of carbohydrate and nitrogen supply in sugarcane bagasse based total mixed ration (TMR) on in situ nutrient degradation. The first experiment was aimed to create three TMR with different synchronization index. Ingredient feedstuffs of TMR were evaluated for its in situ organic matter (OM) and nitrogen (N) degradation kinetics. On the basis of the OM and N degradation kinetics of feedstuffs, three sugarcane bagasse based TMR were formulated with synchronization indexes of 0.37; 0.50; and 0.63; respectively. The TMR had similar levels of crude protein (CP), total digestible nutrients, and neutral detergent fiber (NDF). In the second experiment, the three TMR with different synchronization index were evaluated for in situ degradability characteristics of OM, CP, NDF, and sulfur. The in situ degradation of OM in TMR were decreased (P<0.05) with the increasing of synchronization index. The higher synchronization index in TMR increased (P<0.05) CP degradation of CP. The NDF degradation decreased slightly by the alteration of synchronization index in TMR. The higher synchronization index in TMR reduced (P<0.05) in situ sulfur degradation, and this may not support to effects of synchronization of carbohydrate and nitrogen supply.